1991
DOI: 10.1017/s0252921100064174
|View full text |Cite
|
Sign up to set email alerts
|

CQSSP: A New Technique for Establishing the Tie Between the Stellar and Quasar Celestial Reference Frames

Abstract: Using artificial satellites as transfer objects the project “Coupled Quasar-Satellite-Star Positioning” represents an independent method for linking quasar and stellar reference frames. Optical observations of close approaches between reference stars and satellites yield satellite positions in the stellar reference frame. On the other hand high precision satellite orbits in the International Earth Rotation Service (IERS) terrestrial reference frame are obtained from laser or radiometric observations. Using IER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…As new detectors and observing methods have been introduced in differential astrometry, the astrometric accuracy of ground-based observations have become limited by atmospheric turbulence. Some examples of recent developments in differential astrometry are: the program based on the MAP (Gatewood 1987), utilization of a CCD (Monet et al 1992), the mark III optical interferometer (Shao et al 1990;Hughes and Hutter 1990), close-approach astrometry (Nakamula et al 1991) and narrow-angle astrometry relative to artificial satellites or quasars (Schildknecht et al 1991;Kammeyer et al 1991). It has been shown that atmospheric turbulence is indeed the limiting factor of the MAP's astrometric accuracy (Han 1989b).…”
Section: Introductionmentioning
confidence: 99%
“…As new detectors and observing methods have been introduced in differential astrometry, the astrometric accuracy of ground-based observations have become limited by atmospheric turbulence. Some examples of recent developments in differential astrometry are: the program based on the MAP (Gatewood 1987), utilization of a CCD (Monet et al 1992), the mark III optical interferometer (Shao et al 1990;Hughes and Hutter 1990), close-approach astrometry (Nakamula et al 1991) and narrow-angle astrometry relative to artificial satellites or quasars (Schildknecht et al 1991;Kammeyer et al 1991). It has been shown that atmospheric turbulence is indeed the limiting factor of the MAP's astrometric accuracy (Han 1989b).…”
Section: Introductionmentioning
confidence: 99%